MiR-30c-5p ameliorates hepatic steatosis in leptin receptor-deficient (db/db) mice via down-regulating FASN - Fan, Jiahui (Oncotarget, 2017)
Approximately 15–40% of the general adult population suffers from non-alcoholic fatty liver disease (NAFLD) worldwide. However, no drug is currently licensed for its treatment. In this study, we observed a significant reduction of miR-30c-5p in the liver of leptin receptor-deficient (db/db) mice. Remarkably, recombinant adeno-associated virus (rAAV)-mediated delivery of miR-30c-5p was sufficient to attenuate triglyceride accumulation and hepatic steatosis in db/db mice. Through computational prediction, KEGG analysis and Ago2 co-immunoprecipitation, we identified that miR-30c-5p directly targeted fatty acid synthase, a key enzyme in fatty acid biosynthesis. Moreover, down-regulation of FASN by siRNA attenuated some key features of NAFLD, including decreased triglyceride accumulate and lipid deposition. Our findings reveal a new role of miR-30c-5p in counterbalancing fatty acid biosynthesis, which is sufficient to attenuate triglyceride accumulation and hepatic steatosis in db/db mice.